Color and texture analysis of glucomannan modified growol cookies for diabetic - Puspaningtyas, Desty Ervira; Sari, Puspita Mardika; Styaningrum, Silvia Dewi; Sucipto, Adi; Rahmawati, Dwita Mukti; Lestari, Getha Puji (Poltekkes Kemenkes Aceh, 2024)
Background: Foods high in dietary fiber can provide good glycemic control for diabetics. Growol cookies have been developed as a healthy snack high in dietary fiber.Objectives: Colors and texture examination of Growol cookies need to be done to see the potential for product development.Methods: There are five variants of cookies: negative control growol cookies (cookies A), positive control growol cookies (cookies B), inulin-modified growol cookies (cookies C), 3% glucomannan-modified growol cookies (cookies D), and 7% glucomannan-modified growol cookies (cookies E). Color and texture were examined in triplicate using a chromameter and texture analyzer. Difference tests were carried out using ANOVA and Kruskal-Wallis.Results: There was no difference in brightness among cookies, but there was a difference in the a-value which describes the red color (p=0,001), and the b-value which describes the yellow color among cookies (p=0,038). There were differences in hardness in the first bite (p=0,004) and second bite (p=0,005), cohesiveness (p=0,032), gumminess (p=0,005), fracture (p=0,001), springiness (p=0,035), crispiness peak (p=0,021), crispiness (p=0,005), and crunchiness (p<0,001) among cookies.Conclusion: Colors and textures of cookies B, cookies C, and cookies D tend to be similar to control cookies, so these cookies have the potential to be developed for diabetics.